2008
DOI: 10.1007/s10661-008-0623-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the school drinking water supply and the water quality in Pingtung County, Taiwan

Abstract: In this study, a questionnaire survey of school drinking water quality of 42 schools in Pingtung County was conducted according to the water sources, treatment facilities, location of school as well as different grade levels. Among them, 45% of schools used tap water as the main source of drinking water, and the schools using groundwater and surface water as drinking water source account for 29% and 26%, respectively. The schools above senior high school level in the city used tap water as drinking water more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…The taste threshold of Cu, Zn, and Fe are about 1-2, 0.1-5, and 0.2-0.3 mg/l, respectively ( Table 2). The ideal intake amount of Cu and Zn is 2 and 4-10 mg/day, respectively (Chung et al 2009). The standard for Cu, Zn, and Fe content in drinking water is 1.3, 5, and 0.3 mg/l in Iran, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The taste threshold of Cu, Zn, and Fe are about 1-2, 0.1-5, and 0.2-0.3 mg/l, respectively ( Table 2). The ideal intake amount of Cu and Zn is 2 and 4-10 mg/day, respectively (Chung et al 2009). The standard for Cu, Zn, and Fe content in drinking water is 1.3, 5, and 0.3 mg/l in Iran, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Rural areas are the most affected, and residents resort to the collection of water from wells, ponds, springs, lakes, rivers and rainwater harvesting to meet their domestic water needs [19][20][21][22][23][24]. Water from such sources is often consumed without any form of treatment [12,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…These plants supply dissolved organic compounds, for instance humic substances [26], which directly influence water color, and values of 0.0 TCU are reported due to the low floral density of the study areas. On the other hand, the color of the water is also influenced by the presence of metals, such as iron, and the geology of the areas of the study show high levels of rocks with iron content [10,27,28].…”
Section: Resultsmentioning
confidence: 93%
“…TDS is an indicator that allows knowing the quality of groundwater due to changes in the chemical composition [30,32]; thus, TDS values were reported as 327. 25 Calcium and magnesium carbonate in water represent the total hardness, and these vary with the geology of the area, considerably influencing the taste of the water, although the taste threshold varies between people [27,30,36]. It was found that the springs have a hardness content that varies from 77.70 to 355.80 mg/L in the dry season (p < 0.05), and from 66.10 to 314.20 mg/L in the rainy season (p < 0.05), showing a significant difference between seasons (p = 0.000).…”
Section: Resultsmentioning
confidence: 99%